Analisis Kinerja Rumah Sakit Santo Antonius Jopu DI Ende Nusatenggara Timur dengan Metode Balanced Scorecard dan Swot - Goretti Aran, Maria; Tule, Philipus; Djuang, Gaudensius; A. Manafe, Henny (Dinasti Review Publisher, 2023)
In managing a hospital, it is better to carry out a balanced performance evaluation, namely financial and non-financial. Evaluation like this can be done using the balanced score card and SWOT procedures. The balanced scorecard method supports efforts to realize the hospital's vision, mission, and strategy with long-term goals based on four perspectives, including financial, customer, internal business process, and learning and growth perspectives so that achievements from each perspective can be obtained in an integrated manner. The conclusions obtained in this study are that the financial perspective through effectiveness ratios shows ineffective results, the customer perspective through combined analysis of the results of surveys, interviews and observations, customer satisfaction is quite good, while assessing market share, consumer acquisition, consumer retention and consumer profitability not good and evidenced by a decrease in the number of old and new patients in the last three years (2019 - 2021).